Der Disput zwischen Gustav Rose und Jean-Baptiste Boussingault zum Silber im Uralgold. : Ein Ergebnis der russisch-sibirischen Reise Alexander von Humboldts 1829 - Stottmeister, Ulrich Karl Bernd (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
The French chemist Jean-Baptiste Boussingault, who was encouraged by Alexander von Humboldt, published a new theory on the chemical bond between two metals in 1827. Using the example of silver in pure gold from South American sites, he proved that the two precious metals in this natural alloy were bound together in fixed proportions. The German chemist and mineralogist Gustav Rose, who was also supported by Humboldt, doubted this theory. To prove the opposite, he collected gold samples in the Ural region during Humboldt's Russian-Siberian journey. His analyses showed that there were no bonds between gold and silver, which made a free mixture of the two metals possible. The theoretical justification for this result was not provided until 1926 with the discovery of the ‘Goldschmidt rule’.
Keywords: Pure gold; Natural alloy; chemical analysis; isomorphism; intermetallic compound; Effects of the dispute